The Halalness of Affiliate Commissions on AI-Based Product Promotions from the Perspective of DSN-MUI Fatwa No. 112/DSN-MUI/IX/2017 on Ijarah - Rafika Shahira Adisti; Fatimah Zahara (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
Advances in digital technology are driving the use of artificial intelligence (AI) in affiliate marketing for the creation, management, and distribution of promotional content. The use of AI in product visualization and marketing personalization raises questions regarding the halal status of affiliate commissions when promotions may contain manipulative elements that influence consumer perception. This study aims to analyze the halal status of affiliate commissions in AI-based product promotions based on DSN-MUI Fatwa No. 112/DSN-MUI/IX/2017 regarding the ijarah contract. The study employs a qualitative method with a normative legal approach through the analysis of fatwas, muamalah fiqh literature, and various scientific studies related to affiliate marketing and AI technology, as well as AI-based analysis of affiliate promotional content and consumer comments. The results indicate that affiliate commissions are halal provided that promotions are conducted honestly, transparently, and in accordance with the actual conditions of the product, while fulfilling the principles of clarity regarding the subject matter (ma'qud 'alaih) and compensation (ujrah). Commissions may be considered dubious (syubhat) if the promotion contains hyperbole, visual manipulation, or unclear information that gives rise to gharar and tadlis. The use of AI is permitted as long as it does not mislead consumers and remains consistent with Sharia principles in digital marketing activities.